KEBERFUNGSIAN KELUARGA SEBAGAI BASIS PENGUATAN MODERASI BERAGAMA DI DESA LONDUT AFDELING III KECAMATAN KUALUH HULU KABUPATEN LABUHANBATU UTARA - Ismet Sari; Khairul Hatami Hasibuan; Muhammad Royhan Munthe; Nur Ririn Ridha Hasini; Tiara At-Thahirah Nasution (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2021)
One of the means to teach the differences that exist and also as a place to learn good interactions among differences is by means of religious moderation. And a good place and most importantly a place to learn religious moderation starting from a family. Often there are visible differences starting from the way of worship in religion. And it becomes a problem to cause radicalism. The purpose of this paper is to tell how the initial steps to anticipate in this religious moderation are. And this article discusses that the best place to start the first step to religious moderation is to start with the family. The conclusion from this discussion is that religious moderation needs to be studied so that there is no radical nature in the family, in order to tolerate these differences and lead to the growth of a good and harmonious character from a family to moderate religion towards other families.